Depot Medroxyprogesterone Acetate and the Vaginal Microbiome as Modifiers of Tenofovir Diphosphate and Lamivudine Triphosphate Concentrations in the Female Genital Tract of Ugandan Women: Implications for Tenofovir Disoproxil Fumarate/Lamivudine in Preexposure Prophylaxis. (25th May 2019) - Nicol, Melanie R; Eneh, Prosperity; Nakalega, Rita; Kaiser, Thomas; Kabwigu, Samuel; Isingel, Esther; Beksinska, Mags; Sykes, Craig; Fowler, Mary Glenn; Brown, Todd T; Staley, Christopher; Kiweewa Matovu, Flavia
Abstract: Background: Effective concentrations of antiretrovirals in the female genital tract (FGT) are critical for suppression of viral shedding or effective preexposure prophylaxis. The disposition of tenofovir diphosphate (TFV-DP) and emtricitabine triphosphate (FTC-TP) in the FGT have been previously described. Despite widespread use, however, lamivudine triphosphate (3TC-TP) exposure in the FGT is unknown. Depot medroxyprogesterone acetate (DMPA) and vaginal dysbiosis have been implicated in increased risk of human immunodeficiency virus (HIV) acquisition, but whether they alter TFV-DP or 3TC-TP exposure, and therefore compromise prevention efficacy, is unknown. Methods: Fifty premenopausal women living with HIV in Kampala, Uganda, and receiving daily tenofovir disoproxil fumarate/lamivudine were recruited. Ectocervical biopsies were obtained for quantification of TFV-DP and 3TC-TP using liquid chromatography–mass spectrometry. 16S ribosomal RNA gene sequencing was performed on DNA extracted from vaginal swabs. Wilcoxon rank-sum was used to test for differences between contraceptive groups. Results: 3TC-TP concentrations were on average 17-fold greater than TFV-DP concentrations in cervical tissues. TFV-DP concentrations in cervical biopsies were 76% greater in DMPA users compared with women using nonhormonal contraception (n = 23 per group). Abundance of Lactobacillus in vaginal swabs was correlated with 3TC-TP concentrations in cervical tissues. Conclusions: We found that TFV-DP concentrations were significantly greater in DMPA users compared with women using nonhormonal contraception, suggesting that prevention efficacy is unlikely to be compromised by DMPA use. Similar to reports of FTC-TP, 3TC-TP exposure was significantly greater than TFV-DP in cervical tissue and was correlated with abundance of Lactobacillus. These data support lamivudine as an option for preexposure prophylaxis. Clinical Trials Registration: NCT03377608. Abstract : Tenofovir diphosphate (TFV-DP) and lamivudine triphosphate (3TC-TP) concentrations were quantified in 50 Ugandan women living with human immunodeficiency virus. TFV-DP concentrations were higher in cervical tissue in women using depot medroxyprogesterone, and 3TC-TP concentrations were correlated with Lactobacillus relative abundance.